1999
DOI: 10.1577/1548-8675(1999)019<0696:aessdt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Sampling Survey Design to Estimate Pink Shrimp Population Abundance in Biscayne Bay, Florida

Abstract: We developed an efficient sampling design-based approach using fishery-independent surveys to estimate population abundance of pink shrimp Penaeus duorarum over time in Biscayne Bay, Florida. We initially implemented quarterly stratified random sampling (StRS) using nine habitat strata and determined that average pink shrimp density (numbers/m 2 ) was highest in late fall and lowest in spring and late summer. Coefficient of variation of the quarterly surveys, expressed as percent standard error/mean density, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 15 publications
(13 reference statements)
2
39
1
Order By: Relevance
“…In these cases, the precision levels would enable detection of relative changes in population mean density ranging from 14% to 24% (approximately 2 SEs) in a future time period. The CVs obtained in our study are among the lowest reported for comparable surveys of marine species, e.g., American lobster Homarus americanus (CVs 4%-10%, Smith and Tremblay 2003), pink shrimp Farfantepenaeus duorarum (CVs 6%-14%, Ault et al 1999), and the sea scallop Placopecten magellanicus (CVs 6%-10%, Smith and Lundy 2006). Our survey was generally less precise for species with relatively low densities (<3 colonies/10 m 2 ).…”
Section: Design Performancecontrasting
confidence: 66%
See 2 more Smart Citations
“…In these cases, the precision levels would enable detection of relative changes in population mean density ranging from 14% to 24% (approximately 2 SEs) in a future time period. The CVs obtained in our study are among the lowest reported for comparable surveys of marine species, e.g., American lobster Homarus americanus (CVs 4%-10%, Smith and Tremblay 2003), pink shrimp Farfantepenaeus duorarum (CVs 6%-14%, Ault et al 1999), and the sea scallop Placopecten magellanicus (CVs 6%-10%, Smith and Lundy 2006). Our survey was generally less precise for species with relatively low densities (<3 colonies/10 m 2 ).…”
Section: Design Performancecontrasting
confidence: 66%
“…The estimates of strata variances obtained from the Florida Keys survey will enable application of an optimal allocation strategy in a future survey. Studies have shown, however, that estimates of strata variances become more reliable over several successive surveys (Smith and Gavaris 1993;Ault et al 1999). Thus, it will likely take some time to fully realize gains in efficiency via optimal allocation.…”
Section: Optimizing Future Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Stratified random sampling, commonly used in fishery-independent surveys, usually divides a target survey area into different strata and conducts simple random sampling within each stratum (Cochran, 1977). Stratification can result in an increased precision over a simple random survey design when observations are more homogenous within strata than between strata and the sampling efforts are allocated to strata in proportion to strata size or strata variance (Ault et al, 1999;Manly et al, 2002;Chen et al, 2006;Miller et al, 2007;Lohr, 2009). Thus, an appropriate stratification is important to achieve an improved precision of survey estimates (Ault et al, 1999;Smith and Lundy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the Florida Keys coral reef ecosystem, delineation of fish and shellfish distribution patterns is critically important for efficient fishery-independent monitoring of reef resources (Ault et al 1999(Ault et al , 2005a(Ault et al , 2009Lindeman et al 2000). The iterative process of designing and implementing fish surveys can capitalize on analyses of fish distributional patterns as a means to inform and improve survey design characteristics (Ault et al 2005a;Smith et al 2011aSmith et al , 2011b.…”
mentioning
confidence: 99%